ACCURACY OF AUTOMATED CELL ENUMERATION METHOD FOR VARYING CONCENTRATION OF WBCS FOR VARIOUS BODY FLUID SAMPLES - Brohi, Sana; Shaikh, Muhammad Shariq; Moiz, Bushra (Infectious Diseases Journal of Pakistan, 2023)
Background: Body fluids (BF) including peritoneal, pericardial, pleural, synovial and cerebrospinal fluids are now being analyzed by fully automated methods that are replacing the manual methods. The aim of this study is to assess the accuracy of automated instrument at varying concentrations of WBCs of various body fluid samples. Material and Methods: This cross-sectional study was conducted at the section of Hematology, Department of Pathology and Laboratory Medicine, the Aga Khan University, Karachi, Pakistan from November 2020 to April 2021. Forty body fluid samples with suspicion of infection including peritoneal, pericardial, pleural, synovial and cerebrospinal fluids (CSF) were analyzed to verify accuracy of white blood cells counts on fully automated XN-1000TM hematology analyzer (Sysmex Corporation, Kobe, Japan) against Neubauer chamber method (a manual method of differentiating WBCs via microscopy). The culture results of the body fluid samples were also analyzed. EP Evaluator version 10.3.0.556 (Data Innovations, LLC, VT, US) was used for statistical analysis with other supporting statistics such as Correlation Coefficient (R), Bias, Mean and Standard Deviation were included. Results: Eleven (n=11) of forty (n=40) body fluid samples showed high WBC count above the normal range. Samples with normal WBC (n=29) were also included in accuracy study to assess instrument performance at varying concentration of analyte. An average Error Index of -0.27 (-0.99 to 0.74) for WBC was obtained. Microbiological cultures grew Escherichia. Coli in 1 and Acinetobacter species in 1 CSF samples and Staphylococcus Aureus in 1 pleural sample. Conclusion: The study verified accuracy of varying concentration of WBC counting by fully automated Sysmex XN-1000 analyzer for various body fluid samples. Keywords: Body fluids, Validation, Automated analyzer, Performance specifications, Accuracy verifications, High white blood count, Infectious.